1999
DOI: 10.1557/jmr.1999.0208
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Loading, Residual Stresses, Shakedown, and Tribology

Abstract: Protective residual stresses may be developed in the near surface layers of tribological contacts which enable loads sufficiently large to cause initial plastic deformation to be accommodated purely elastically in the longer term. This is the process of shakedown and, although the underlying principles can be demonstrated by reference to relatively simple stress systems, the situation is complex under a moving Hertzian pressure distribution. Bounding theorems can be used to generate appropriate load or shakedo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…A solution of this problem can also be useful for rough surfaces wear studies (Kapoor et al, 2002) and for contact shakedown in various rolling elements, see e.g. a review by Williams et al (1999). This review relates to problems where the elastic limit is not greatly exceeded, and hence the contact is assumed Hertzian.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A solution of this problem can also be useful for rough surfaces wear studies (Kapoor et al, 2002) and for contact shakedown in various rolling elements, see e.g. a review by Williams et al (1999). This review relates to problems where the elastic limit is not greatly exceeded, and hence the contact is assumed Hertzian.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review of repeated loading of an elastic-plastic half-space can be found in Williams et al (1999). Repeated loading, protective residual stresses and shakedown theory applied to tribology studies are presented.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, according to the Hertz solution maximum effective stress and consequently strain are reached at the depth of 0.785 of half contact length b (e.g. see Williams et al, 1999), but in the experiments maximum hardness increment and hence maximum strain were observed at the depth of (1.5-2) b. This is apparently due to the descending nature of the distribution of material hardness in the transition zone of the hardened layer.…”
Section: Experimental Observationmentioning
confidence: 82%
“…By contrast, when shakedown is not possible, so that each load cycle is accompanied by an element of incremental plasticity, component lives are much curtailed. When shakedown does occur it may do so as rapidly as the second application of the load or it may take many cycles to become established -such variations depend on the effective hardening behaviour of the material in question [29,30].…”
Section: Shakedown and Shakedown Mapsmentioning
confidence: 99%